2003
DOI: 10.1002/jso.10246
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fas (sFas) and soluble Fas ligand (sFas‐L) balance in laryngeal carcinoma before and after surgical treatment

Abstract: The decrease in sFas and sFas-L levels after surgery suggest that they may be produced by or closely linked to tumour cells. Larger prospective clinical studies of patients with LSCC will be needed to establish the clinical significance of sFas and sFas-L, as reported for other neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[1][2][3]5,7,12 It was also confirmed in several studies that surgical removal of tumors reduced sFas levels. 4,13,14 As Holdenrieder and Stieber described in their review, 15 cancer itself has some self-defense mechanisms for avoiding apoptosis, one of which must be sFas.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5,7,12 It was also confirmed in several studies that surgical removal of tumors reduced sFas levels. 4,13,14 As Holdenrieder and Stieber described in their review, 15 cancer itself has some self-defense mechanisms for avoiding apoptosis, one of which must be sFas.…”
Section: Discussionmentioning
confidence: 99%
“…sFas is one of the alternatively spliced variants of Fas which does not have the transmembrane domain and thus is readily secreted [Cheng et al, 1994]. Serum levels of sFas are reported to be higher in cancer patients, including those with SCCHN, than in healthy controls [Knipping et al, 1995;Alecu et al, 2002;Furuya et al, 2003;Pignataro et al, 2003]. Although sFas was detected in culture supernatants of SCCHN cells, its levels did not correlate with the susceptibility of these cells to Fas-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Also Pignataro et al 9 found that the loss of Fas receptors is a common feature of most human malignancies and are associated with the progression of cancers, including SCCHN. Therefore, the variants of the Fas could be expected to have an effect on cell death, and thus, carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Fas and its specific ligand (Fas-L), both of which are involved in apoptosis, exist in membranebound and soluble forms(sFas). 9 Because of the role of the Fas genes in regulating cell death, and because abnormal expression of Fas have been observed in a variety of tumors, including SCCHN, we assess serum sFas levels in patients with different stages of laryngeal squamous cell carcinoma (LSCC) according to TNM classification to investigate its prognostic significance, we also correlate its level with the host immune response via the ultrastructural study of the buffy coat.…”
Section: Introductionmentioning
confidence: 99%